Associations between kindergarten climate and retention intention of kindergarten teachers: The chain mediating roles of perceived organizational support and psychological empowerment - Shi, Dasheng; Zhang, Mengmeng; Wang, Yan; Xu, Yongqi; Yang, Xiantong (Frontiers in Psychology, 2022)
Kindergarten climate has been reported to be closely associated with teacher's retention intention, yet the underlying mechanism of this association remains unclear in some ethnic minority areas in China. Based on the Personal -Environment Fit Theory and Organizational Support Theory etc., the research aims to examine the correlation between kindergarten climate and retention intention of Chinese kindergarten teachers in ethnic minority areas, and the chain mediating role of perceived organizational support, as well as the psychological empowerment. 1199 Chinese kindergarten teachers were recruited from ethnic minority areas to complete the questionnaires. Based on their responses, the main findings of the study were listed as following: 1) a supportive kindergarten climate has a positive correlation to perceived organizational support, psychological empowerment, retention intention. 2) a positive kindergarten climate would increase the retention intention only through the indirect path of perceived organizational support, psychological empowerment, as well as the chain mediating path between these two variables. Taken together, these results further explained the interplay between kindergarten climate and teachers' retention intention. Implications for research on retention intention were discussed. Theoretically, it enriches the theoretical basis related to the external environmental resources and individual cognition. Practically, it means that educational policymakers will need to issue new guidelines to ensure that more kindergarten teachers are retained in China's ethnic minority areas.